2002
DOI: 10.3168/jds.s0022-0302(02)74166-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of Oligosaccharides in Yogurt Containing Bifidobacteria and Yogurt Cultures

Abstract: Yogurts were prepared by using yogurt cultures combined to mixed cultures of bifidobacteria (Bifidobacterium animalis, Bifidobacterium bifidum, Bifidobacterium breve, Bifidobacterium infantis, and Bifidobacterium longum) and by adding a preincubation step (1.5 h at 50 degrees C) with bifidobacteria to the conventional method of manufacture in order to produce oligosaccharides. The survival of bifidobacteria was drastically affected during storage of yogurts, except for products containing B. animalis, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
7
38
0
3
Order By: Relevance
“…Due to the poor growth of bifidobacteria in milk, it is generally recommended that their inoculation level in fermented milk should be that of the desirable level of the probiotic culture in the final product. However, increased inoculum does not guarantee viability of bifidobacteria during fermentation and storage of fermented milk, which has been described as variable depending on the species and supplements added [48], [49]. Physicochemical properties of probiotic yogurt samples were shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the poor growth of bifidobacteria in milk, it is generally recommended that their inoculation level in fermented milk should be that of the desirable level of the probiotic culture in the final product. However, increased inoculum does not guarantee viability of bifidobacteria during fermentation and storage of fermented milk, which has been described as variable depending on the species and supplements added [48], [49]. Physicochemical properties of probiotic yogurt samples were shown in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…In order to produce oligosaccharides from raffinose and/ or stachyose in for example soymilk this The structure of these oligomers indicated that selective transglycosylation took place at the C6-hydroxyl group. Contrary to the example provided by Lamoureux et al [14], these oligosaccharides should be added as ingredient to a probiotic strain to obtain a synbiotic, and are not produced in the product itself. The genome sequence of B. longum revealed that most glycosyl hydrolases contain no signal peptide and are thus not secreted [24].…”
Section: Application Of Transglycosylation Products In Dairy Sciencementioning
confidence: 95%
“…It is also possible to use the transglycosylation activity of enzymes from probiotic microorganisms to synthesize prebiotics in food products. Lamoureux et al [14] used mixed cultures of bifidobacteria in the preparation of yoghurts. These bifidobacteria contained β-galactosidase activities that were responsible for the extracellular production of oligosaccharides with a polymerization degree of 3 from lactose.…”
Section: Application Of Transglycosylation Products In Dairy Sciencementioning
confidence: 99%
“…Loss of viability of probiotics during the fermentation process and refrigerated storage is identified as a major issue in the production of fermented probiotic products. It is being reported that the viable cells of bifidobacteria in yoghurt-like product could not be maintained in sufficient amounts (>10 6 cfu/g) for more than 1 week during storage at 4 °C (Roy et al 1997, Lamoureux et al 2002. Based on the results obtained from the storage study, it is quite clear that the developed product served as a good carrier of probiotic organism even after 60 days of storage at refrigeration temperature.So it could be suggested that development of such products will be an attractive alternative to counter the issues like loss of probiotic viability and stability pertaining with the fermented milk products.…”
Section: Discussionmentioning
confidence: 97%